Genetic diversity of Rhizobia isolates from Amazon soils using cowpea (Vigna unguiculata) as trap plant - Silva,F.V. (2012)
The aim of this work was to characterize rhizobia isolated from the root nodules of cowpea (Vigna unguiculata) plants cultivated in Amazon soils samples by means of ARDRA (Amplified rDNA Restriction Analysis) and sequencing analysis, to know their phylogenetic relationships. The 16S rRNA gene of rhizobia was amplified by PCR (polymerase chain reaction) using universal primers Y1 and Y3. The amplification products were analyzed by the restriction enzymes HinfI, MspI and DdeI and also sequenced with Y1, Y3 and six intermediate primers. The clustering analysis based on ARDRA profiles separated the Amazon isolates in three subgroups, which formed a group apart from the reference isolates of Bradyrhizobium japonicum and Bradyrhizobium elkanii. The clustering analysis of 16S rRNA gene sequences showed that the fast-growing isolates had similarity with Enterobacter, Rhizobium, Klebsiella and Bradyrhizobium and all the slow-growing clustered close to Bradyrhizobium.